BAGAIMANA MERANCANG SISTEM MANAJEMEN KINERJA? - Wienda P. Rahardja; Margaretha Banowati Talim; Albert Kurniawan Purnomo (Jurnal Manajemen Maranatha, 2018)
This research proposes a performance management model based on existing theories, the concept to be developed using qualitative methods. The purpose of this paper was to find the model of performance management system with benchmarking and balanced scorecard approach. The challenge of this research is the implementation of this design model is still a few companies in Indonesia who can apply it. The final implication of this research is to provide a complex model of performance management system for companies that need and will implement it, as well as relevant for practitioners and academics, as it clarifies existing knowledge and provides a platform for further research. Keywords: Performance Management, Performance Measurement, Benchmarking, Balanced Scorecard, KPI